ETNIS BUGIS DI KEPULAUAN KARIMUNJAWA: Harmoni dalam Pelestarian Budaya dan Tradisi - Suliyati, Titiek (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
Karimunjawa islands possess several unique ethnicities. As the biggest island of the 27 islands, Karimunjawa has a variety of ethnic groups such as Java, Bugis, Madura, Buton, Bajao, and Flores. As the biggest ethnic comes from outer Karimunjawa, they live in group in Kemojan village, Batulawang. They still carry out their culture and tradition from their mother land. It is not suprising that a lot of Bugis-design houses can be found in Batulawang. Bugis society also occupies Parang island, but they already lost their ethnic characteristics, even they live like Javanese people in term of their houses and language. Life philosophy of Bugis people may build harmony among other ethnic groups in Karimunjawa. Pluralism can be seen in everyday life among people who live Karimunjawa. Proporsionally, a variety of ethnics who live in Karimunjawa gives honour and confession toward activities, social values, social structure and organization. Karimunjawa people already welcome the pluralism in their social lives.